Multifunctionalized Polyamides Prepared by Facile Ugi Reaction as Thermosensitive, Biocompatible and Antibacterial Biomaterials. Issue 9 (3rd March 2020) - Liu, Na; Fu, Congcong; Zhang, Qi; Zhao, Ronghui; Sun, Zhuxing; Zhang, Pengfei; Ding, Lan; Deng, Kuilin
Abstract: A series of multifunctionalized polyamides were facilely prepared by Ugi four‐component polymerization (Ugi‐4CP) in one‐pot method at room temperature using several diacids, aldehydes, 1, 4 bis‐( 3 ‐aminopropyl) piperazine and tert ‐butyl isocyanide as monomers. The simple combination of monomers in Ugi‐4CP led to formation of nine thermosensitive polyamides in water, and their lower critical solution temperatures (LCSTs) were in range of 13.1‐70.1°C. The LCSTs for the subsequently‐quaternized polyamides (PBA‐800‐Br, PIA‐800‐Br and PCA‐800‐Br) were easily readjusted to the desired value in the inorganic salt solutions. PBA‐800‐Br and PIA‐800‐Br exhibited high antibacterial activity against Gram negative E. coli and Gram positive S. aureus . Confocal laser scanning microscope (CLSM) manifested the clear internalization into the cellular inside for the fluorescent molecule‐labelled polyamides. After 24–72 hours of incubation in polyamide solution, the viability rate of HeLa cells reached up to 80–141%, indicating the excellent biocompatibility. In conclusion, the thermosensitive, antibacterial and biocompatible polyamides have great potential to be used as biomaterials. Abstract : As the great potential biomaterials, the thermosensitive, antibacterial and biocompatible polyamides were facilely prepared by Ugi four‐component polymerization ( Ugi‐4CP) in the air, at room temperature and by one‐pot method. Additionally, Ugi‐4CP provides a powerful tool for the multi‐functionalization of polyamides because of the diversity of components in the reaction.